Long-term outcomes of children with transanal endorectal pull-through and a review of the literature. Issue 6 (1st November 2016) - Erginel, Basak; Gun Soysal, Feryal; Keskin, Erbug; Celik, Aladdin; Yüksel, Secil; Salman, Tansu
Abstract: Introduction: The transanal endorectal pull-through (TERPT) procedure, the latest advancement in the surgical treatment of Hirschsprung's disease, has replaced most other surgical techniques in the last decade. Patients and methods: Between October 2002 and March 2014, a total of 22 patients diagnosed with Hirschsprung's disease underwent a one-stage TERPT operation. Results: Resected segments included the rectosigmoid (seven patients), the descending colon (10 patients), and the transverse colon (five patients). The minimum length of the resected segments was 15 cm and the maximum length was 65 cm. The mean length was 39.18 ± 12.05 cm. Following surgery, the start of oral ingestion was 1–8 days (mean 3 ± 1.69 days) and the hospital stay after the operation lasted 4–11 days (mean 7.04 ± 2.05 days). The mean follow-up period was 48 ± 6 months (range of 24–166 months). Out of 22 patients, three patients had an anal stricture, which responded to anal dilatations; three patients had an enterocolitis episode that required hospitalization; two patients experienced constipation; and two patients had incontinence/soiling. Conclusion: Our data suggest that the TERPT operation can be safely performed in terms of long-term complications.